2021
DOI: 10.1001/jamacardio.2021.2537
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Capacity in Young Adults Born Small for Gestational Age

Abstract: Being born small for gestational age (SGA), approximately 10% of all births, is associated with increased risk of cardiovascular mortality in adulthood, but mechanistic pathways are unclear. Cardiac remodeling and dysfunction occur in fetuses SGA and children born SGA, but it is uncertain whether and how these changes persist into adulthood.OBJECTIVE To evaluate baseline cardiac function and structure and exercise capacity in young adults born SGA. DESIGN, SETTING, AND PARTICIPANTSThis cohort study conducted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 37 publications
4
26
0
Order By: Relevance
“…[13] reported a negative effect of prematurity on diastolic filling of the left ventricle, likely caused by an immature myocardium [14,38,39]. Similarly, data from Crispi et al [38] and McKay et al [40] indicate that the impaired early filling was accompanied by a reduced cardiac output, suggesting that the heart of prematurely born humans likely provides a reduced blood supply to working muscles during exercise, which would impair aerobic exercise capacity [41,42].…”
Section: Reduced Maximal Aerobic Exercise Capacity: a Problem Of O 2 ...mentioning
confidence: 99%
See 2 more Smart Citations
“…[13] reported a negative effect of prematurity on diastolic filling of the left ventricle, likely caused by an immature myocardium [14,38,39]. Similarly, data from Crispi et al [38] and McKay et al [40] indicate that the impaired early filling was accompanied by a reduced cardiac output, suggesting that the heart of prematurely born humans likely provides a reduced blood supply to working muscles during exercise, which would impair aerobic exercise capacity [41,42].…”
Section: Reduced Maximal Aerobic Exercise Capacity: a Problem Of O 2 ...mentioning
confidence: 99%
“…[13] reported a negative effect of prematurity on diastolic filling of the left ventricle, likely caused by an immature myocardium [14,38,39]. Similarly, data from Crispi et al [38] and McKay et al [40] indicate that the impaired early filling was accompanied by a reduced cardiac output, suggesting that the heart of prematurely born humans likely provides a reduced blood supply to working muscles during exercise, which would impair aerobic exercise capacity [41,42]. Whether the reduced stroke volume previously reported is simply an effect of the smaller left ventricle because of reduced filling [43,44] (and thus indicating more of a systemic influence of the circulating blood volume instead of impaired heart muscle function itself), or whether there is an intrinsic impairment in myocardial contraction and/or relaxation remains to be determined.…”
Section: Reduced Maximal Aerobic Exercise Capacity: a Problem Of O 2 ...mentioning
confidence: 99%
See 1 more Smart Citation
“…During oxygen deprivation, the heart will try to cope with this shortage by changing its shape in order to ensure oxygen availability to the principal organs. Firstly, it may develop a more spherical shape to maintain systolic volume, and if the situation persists, cardiac hypertrophy develops to increase contractility [ 56 , 57 , 58 ]. Again, not surprisingly, both miR-132-3p and miR-25-3p target the MEIS1 gene ( Figure 6 ), which is mainly involved in cardiomyocyte differentiation and cardiac muscle hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, children born IUGR have been shown to have smaller hearts with non‐hypertrophic spherical ventricles and impaired relaxation, all independent of body size (Sarvari et al, 2017). Although preterm‐born children with IUGR have been shown to have the greatest cardiac remodeling (Sarvari et al, 2017), alterations have also been observed by echocardiography and CMR imaging in mild IUGR cases born at term (Crispi et al, 2010, 2021) suggesting a distinct contribution of IUGR on the cardiac phenotype of prematurity.…”
Section: The Role Of Maternal and Early Life Environmentmentioning
confidence: 99%